Con: clinical remission in asthma – not yet there - Lauren Eggert; Sarah Rhoads; Michael E. Wechsler; Praveen Akuthota (European Respiratory Review, 2025)
The ideal definition of asthma remission should be practical, measurable and meaningful for both patients and physicians, while also representing true disease modification. Unfortunately, current proposals to define asthma remission fall short of this standard, not for lack of careful consideration, but due to the challenges presented by asthma, including but not limited to variability in symptom perception, intrinsic variability in lung function, seasonality and the impact of comorbidities. This article discusses obstacles and challenges to developing a widely adopted, consensus definition of asthma remission. We searched the literature for keywords including “asthma”, “remission” and “super-responder” and identified interventional trials in asthma that highlight the challenges inherent in defining asthma remission.